Malathion-Induced Hematoxicity and Its Recovery Pattern in Barbonymus gonionotus - Cynthia E. Mrong; Md. R. Islam; Kamrunnaher Kole; Nusrat N. Neepa; Md. J. Alam; Md. R. Haque; Umme O. Rahman; Golam M. Mostakim (Journal of Toxicology)
An experiment was conducted to assess malathion-induced hematological responses of Barbonymus gonionotus (silver barb) and its recovery patterns in malathion-free water. Fish (45 days old) were exposed to two sublethal concentrations, namely, 25% and 50% (i.e., 3.78 and 7.56 ppm) of LC50 (15.13 ppm) of malathion for 28 days, followed by a postexposure recovery period for the same time. The hematological parameters were examined after 1, 7, 14, 21, and 28 days of exposure as well as after the postexposure recovery time. Except in the case of the control group (0% of malathion), the obtained results revealed that malathion exposure resulted in significantly (p<0.05) higher prevalence and severity of micronucleus and lower values of Hb, PCV, and RBC and significantly higher values of WBC in a concentration- and time-dependent manner. The values of blood glucose, MCV, MCH, and MCHC showed mixed trends during the experiment. During the recovery period, all blood parameters (micronucleus, glucose, Hb, PCV, RBC, WBC, MCV, MCH, and MCHC) partially recovered, which means that the recovery period was not long enough for the organisms to recover from the previous exposure. The study thus confirms that hematology is a sensitive indicator for fish to detect toxicity caused by different chemicals. Changes in these parameters can provide useful information about environmental conditions and risk assessment of aquatic organisms.